Conceptualizing Islamic character education: a theoretical analysis based on the Qur’an and Hadith - Syafe’i, Syafe’i; Anwar, Abu; Aulia Sukhairani, Raihana (UIR Press, 2026)
The growing concern over moral decline, identity fragmentation, and ethical challenges in contemporary society has intensified scholarly interest in character education, yet limited attention has been given to reconstructing Islamic character education through a comprehensive conceptual framework grounded in the Qur'an and Hadith. This study aims to reconceptualize Islamic character education by systematically analyzing its philosophical foundations, core dimensions, and educational implications through a qualitative concept analysis. Employing a qualitative library research design, the study examines primary Islamic sources, including the Qur'an and authentic Hadith, alongside contemporary literature on character education and moral development. Data were analyzed through iterative processes of concept identification, categorization, comparison, and theoretical synthesis to reconstruct an integrated conceptual framework. The findings demonstrate that Islamic character education is founded on the interconnected principles of fitrah (innate human disposition), tawhid (the unity of God), tazkiyah (spiritual purification), and akhlāq karīmah (virtuous character), which collectively integrate cognitive, moral, spiritual, emotional, and behavioral dimensions of human development. Furthermore, the study identifies substantial conceptual convergence between Islamic character education and contemporary theories of moral development while revealing the distinctive contribution of Islamic epistemology in positioning spiritual consciousness as the foundation of ethical behavior. This study proposes a holistic conceptual framework that advances the theoretical discourse on Islamic character education and provides a foundation for curriculum development, pedagogical innovation, and character-based educational policies in contemporary Islamic educational institutions.